Environmental exigencies and the efficient voter rule - David A. Anderson (Economies, 2020)
Externality problems hinder solutions to existential threats, including climate change and mass extinction. To avert environmental crises, policymakers seek mechanisms that align private incentives with societal exigencies. Successful solutions bring individuals to internalize the broad repercussions of their behavior. In some cases, privatization, Coasian bargaining, or Pigouvian taxes effectively place the weight of externalities on the relevant decision makers. Yet, the available remedies often fail to provide satisfactory outcomes, and inefficiencies persist in the markets for energy, transportation, and manufactured goods, among others. This article explains how a simple voting mechanism can achieve socially optimal decisions about many of the innumerable externality problems that remain.
Keywords: G50; 330; efficient voter rule; environmental protection; externalities; social cost